Agriculture advisory service Požarevac in the function of the improvement of agriculture production in Braničevo district - Zdravković, Marina (Array, 2019)
The advisory service in the Republic of Serbia is specific, has a long tradition, has undergone significant organizational changes, and today's agrarian structure is characterized by a large number of agricultural holdings with a relatively small number of agricultural advisers. The agricultural advisory service is important for the improvement of agricultural production, because the quality of the advisory work determines the speed of progress in agriculture, and in that sense it is important to perceive the factors influencing its functioning and the attitudes of the employees' advisors. A survey disputed in PSS Požarevac was mirrored in the interview of five advisers working on the improvement of agricultural production in the Braničevo district, within the framework of the advisory service. The advisers expressed their views on the characteristics of the organization and the advisory work they deal with, the cooperation with agricultural producers, highlighted the difficulties they face in their efforts to achieve better functioning of the service and provided suggestions for improving advisory and cooperation with farmers, all with the aim improving the quality of agricultural production.